Metal-Free Synthesis of S-Aryl Dithiocarbamates: A Direct Approach from Anilines and Secondary Amines in the Presence of tert-Butyl Nitrite - Narayanan, Aswathi C; Singh, Sundaram; Kandasamy, Jeyakumar (Synlett, 2025)
A simple and efficient method was developed for the preparation of S-aryl dithiocarbamates from anilines, carbon disulfide, and amines in acetonitrile–water. The reactions proceeded at room temperature in the absence of catalysts, and the desired products were obtained in good to excellent yields. Simple operations, easy access to reactants, catalyst-free conditions, and high product yields are key benefits of this method.
Keywords: dithiocarbamates; anilines; amines; metal-free reaction; diazo compounds